Functions of language in forest resource report genre from a systemic functional linguistics perspective - Wan Farah Wani Wan Fakhruddin, 1983-, author; Hanita Hassan, 1971-, supervisor; Akademi Bahasa (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Ph.D) - Universiti Teknologi Malaysia, 2017